Is learning mathematics still creative and enjoyable during the COVID-19 pandemic? - Leomarich Casinillo (Universitas Djuanda, 2022)
Creativity in learning is an enjoyable experience for most students who are studying mathematics. However, when the COVID-19 pandemic brought unprecedented experiences to students, learning mathematics is questionably creative and enjoyable nowadays. This study intends to measure the level of creativity and how enjoyable is learning mathematics amidst the pandemic. The study develops statistical models to capture the different factors that significantly influence the students' creativity and enjoyable experience in learning mathematics. A selected secondary data from the existing study was utilized and analyzed through some descriptive measures and a regression method as well as its diagnostics. Results revealed that the mean perception scores (scale of 1 to 10) for the level of creativity and enjoyment are 5.27 and 5.17, respectively. This implies that there is only moderate creativity and enjoyment in learning mathematics amidst the pandemic. Findings showed that the predictors of students' level of creativity in learning mathematics are